The 2024 top 10 list of endoscopy topics in medical publishing: an annual review by the American Society for Gastrointestinal Endoscopy Editorial Board - Martinez, Melissa; Bartel, Michael J.; Chua, Tiffany; Dakhoul, Lara; Fatima, Hala; Glessing, Brooke; Jensen, Dennis; Lara, Luis F.; Shinn, Brianna; Tadros, Micheal; Villa, Edward; Saltzman, John R. (Gastrointestinal endoscopy, 2025)
Using a systematic literature search of original articles published during 2024 in Gastrointestinal Endoscopy (GIE) and other high-impact medical and gastroenterology journals, the GIE Editorial Board of the American Society for Gastrointestinal Endoscopy compiled a list of the top 10 most significant topic areas in general and advanced GI endoscopy during the year. Each GIE Editorial Board member was directed to consider 3 criteria in generating candidate topics: significance, novelty, and impact on clinical practice. Subject matter consensus was facilitated by the Chair through electronic voting of the entire GIE Editorial Board. The top 10 identified topics collectively represent advances in the following endoscopic areas: glucagon-like peptide-1 receptor agonists and endoscopy, advances in AI in endoscopy, ergonomics in endoscopy, peroral endoscopic myotomy, bariatric and metabolic endoscopy, endoscopic resection in the colon, gastric intestinal metaplasia and endoscopy, inflammatory bowel disease and endoscopy, GI bleeding risk stratification and endoscopic therapies, and therapeutic EUS. Board members were assigned a topic area and summarized relevant and important articles, thereby generating this overview of the “top 10” endoscopic advances of 2024.